2008
DOI: 10.1109/led.2008.2004568
|View full text |Cite
|
Sign up to set email alerts
|

Uncooled Infrared Imaging Using a Substrate-Free Focal-Plane Array

Abstract: A substrate-free 160 × 160 focal-plane array (FPA) with a 60-µm × 60-µm pitch has been developed and used for an optical readout uncooled infrared (IR) detector. The supporting frame of the FPA is a temperature-variable one due to its large decreases in both heat capacity and thermal conductance. This thermal characteristic significantly increases the temperature change of the microcantilever, which depends on both the temperature change induced by its absorption of IR radiation and the linear superposition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
(16 reference statements)
2
10
0
Order By: Relevance
“…However, the image quality of FPAs operating in air is poor, mainly due to the decreased microstructures' Q−factor. In 2009 the USTC/CAS group has published their final paper [111] with achievements of a 60 μm pitch 160×160 pixel substrate−free FPA, read out with a 4f optical configuration using a knife−edge filter, with a performance of 330 mK NETD, 16 ms time constant and 30 Hz 12−bit imaging (CCD) [112]. Since 2009 numerous articles were published by BIT and the Peking University addressing THz detection [113], signal processing impro− vement techniques [114] and tri−band detection [107].…”
Section: Developments In Chinamentioning
confidence: 99%
“…However, the image quality of FPAs operating in air is poor, mainly due to the decreased microstructures' Q−factor. In 2009 the USTC/CAS group has published their final paper [111] with achievements of a 60 μm pitch 160×160 pixel substrate−free FPA, read out with a 4f optical configuration using a knife−edge filter, with a performance of 330 mK NETD, 16 ms time constant and 30 Hz 12−bit imaging (CCD) [112]. Since 2009 numerous articles were published by BIT and the Peking University addressing THz detection [113], signal processing impro− vement techniques [114] and tri−band detection [107].…”
Section: Developments In Chinamentioning
confidence: 99%
“…A second design implements focal plane arrays using a microcantilever sensor as the thermally sensitive element. This architecture requires additional optical readout devices, such as charge coupled devices (CCDs) or CMOS cameras [7], [8]. The optical readout device introduces vibration, thermomechanical noise and shot noise, which can impair the microbolometer performance.…”
Section: Introductionmentioning
confidence: 99%
“…[3−10] One of the most significant achievements is the strategy of the substrate-free FPA. [8] Its architecture is substantially different from the conventional design, there are no electrical connections or onboard electronics, and the substrate material underneath the effective absorbing area is completely removed. Early experiments have shown that the substrate-free FPA not only provides an unobstructed optical path for IR radiation, but also greatly improves the performance of IR detection to several times higher than the conventional substrate FPA.…”
mentioning
confidence: 99%
“…Using the finite element analysis (FEA), the substratefree FPA has been discussed rigorously, and it was found that the thermal response of the substrate-free FPA would be estimated by comprehensive analysis of the heat affected zone better than a single pixel. [8,9] However the FEA has the disadvantages of being both complex and time consuming, especially when the array size of the FPA is larger and larger. In this Letter, an equivalent circuit model to the substrate-free FPA is presented and applied to identify the performance of IR imaging at atmospheric pressure.…”
mentioning
confidence: 99%
See 1 more Smart Citation